Brain macrostructure correlates of financial altruism in older adults without dementia - Laura Fenton; Gali H. Weissberger; Lauren E. Salminen; Anya Samek; Daisy T. Noriega-Makarskyy; Cassidy P. Molinare; Jordan Williams; Emma Oyen; Paige Kim; Jenna Axelrod; Laura Mosqueda; Hussein Yassine; et al. (Brain Imaging and Behavior, 2026)
Greater financial altruism (i.e., the tendency to give money to an anonymous individual) has been previously associated with poorer performance on neuropsychological tests sensitive to cognitive changes occurring in early Alzheimer’s disease (AD). While these findings provide initial support for the idea that financial altruism may be associated with early AD-related brain changes, no study has used MRI to investigate structural brain correlates of financial altruism in older adults. To address this gap in the literature, the current study investigated associations between brain macrostructure and financial altruism in 101 older adults free from dementia (mean age = 68.45±7.15, mean education = 16.61±2.14, 76% female, 73% White) using a high-field 7 Tesla MRI. Results revealed no significant associations between financial altruism and a priori regions of interest (entorhinal cortex, hippocampus, ventromedial prefrontal cortex, dorsolateral prefrontal cortex, and temporoparietal junction) in the entire sample. However, there was a significant interaction between financial altruism and income, whereby greater financial altruism was associated with lower hippocampal volume in those with a reported income below $100,000. Collectively these results suggest that financial altruism in the context of lower income, but not financial altruism in general, may reflect suboptimal brain aging, and perhaps greater risk of conversion to AD.

Elevated vascular endothelial growth factor a is associated with disruption of default network connectivity in older adults - Arunima Kapoor; Jung Yun Jang; Allison C. Engstrom; Trevor Lohman; Shubir Dutt; John Paul M. Alitin; Isabel J. Sible; Anisa Marshall; Fatemah Shenasa; Aimee Gaubert; Amy Nguyen; David Robert Bradford; et al. (Brain Imaging and Behavior, 2025)
Vascular Endothelial Growth Factor A (VEGF-A) is an angiogenic signaling protein involved in the maintenance of the cerebral vasculature. No prior study has explored whether plasma VEGF-A levels may be associated with brain functional connectivity changes, such as disruption of the default mode network (DMN), which often precedes the development of cognitive changes in aging. Seventy-six independently living older adults (mean age = 70.3 years; SD = 7.5; 31.6% male) free of dementia or clinical stroke underwent venipuncture and brain MRI. Plasma was assayed for VEGF-A. Using resting state functional MRI, region of interest (ROI) to ROI connectivity and graph theory analysis were conducted to determine average connectivity and global efficiency between each of the following ROIs comprising the DMN: medial prefrontal cortex, lateral parietal cortex and precuneus cortex. Multiple linear regression analysis revealed a significant negative association between VEGF-A levels and DMN connectivity (B = − 0.14, 95% CI (-0.26, − 0.01), p =.038), accounting for age, sex, education, and vascular risk factors. Graph theory analysis similarly revealed that VEGF-A levels are associated with global efficiency of the entire network (B = − 0.18, p =.004). These findings suggest that VEGF-A may be elevated early in the progression of neurocognitive disorders. Whether higher levels of VEGF-A contribute to the pathogenesis of neurocognitive disorders or play a protective role in preserving cognitive function warrants further investigation. Clinical Trial Number: N/A; None.

Associations between structural neuroimaging markers of Alzheimer’s risk and scam susceptibility - Melissa Lamar; Konstantinos Arfanakis; Alifiya Kapasi; S. Duke Han; David A. Bennett; Lei Yu; Patricia A. Boyle (Brain Imaging and Behavior, 2024)

Self-reported experiences of discrimination in older black adults are associated with insula functional connectivity - S. Duke Han; Melissa Lamar; Debra Fleischman; Namhee Kim; David A. Bennett; Tené T. Lewis; Konstantinos Arfanakis; Lisa L. Barnes (Brain Imaging and Behavior, 2021)

White matter correlates of scam susceptibility in community-dwelling older adults - Melissa Lamar; Konstantinos Arfanakis; Lei Yu; Shengwei Zhang; S. Duke Han; Debra A. Fleischman; David A. Bennett; Patricia A. Boyle (Brain Imaging and Behavior, 2020)

White matter correlates of temporal discounting in older adults - S. Duke Han; Konstantinos Arfanakis; Debra A. Fleischman; Lei Yu; David A. Bennett; Patricia A. Boyle (Brain Structure and Function, 2018)

Correction to: Detectable Neuropsychological Differences in Early Preclinical Alzheimer’s Disease: a Meta-Analysis - S. Duke Han; Caroline P. Nguyen; Nikki H. Stricker; Daniel A. Nation (Neuropsychology Review, 2017)

Detectable Neuropsychological Differences in Early Preclinical Alzheimer’s Disease: A Meta-Analysis - S. Duke Han; Caroline P. Nguyen; Nikki H. Stricker; Daniel A. Nation (Neuropsychology Review, 2017)

Grey matter correlates of susceptibility to scams in community-dwelling older adults - S. Duke Han; Patricia A. Boyle; Lei Yu; Konstantinos Arfanakis; Bryan D. James; Debra A. Fleischman; David A. Bennett (Brain Imaging and Behavior, 2016)

Gray-matter macrostructure in cognitively healthy older persons: associations with age and cognition - Debra A. Fleischman; Sue Leurgans; Konstantinos Arfanakis; Zoe Arvanitakis; Lisa L. Barnes; Patricia A. Boyle; S. Duke Han; David A. Bennett (Brain Structure and Function, 2014)

Beta amyloid, tau, neuroimaging, and cognition: sequence modeling of biomarkers for Alzheimer’s Disease - S. Duke Han; Jonathan Gruhl; Laurel Beckett; Hiroko H. Dodge; Nikki H. Stricker; Sarah Farias; Dan Mungas (Brain Imaging and Behavior, 2012)

CSF biomarker associations with change in hippocampal volume and precuneus thickness: implications for the Alzheimer’s pathological cascade - Nikki H. Stricker; Hiroko H. Dodge; N. Maritza Dowling; S. Duke Han; Elena A. Erosheva; William J. Jagust (Brain Imaging and Behavior, 2012)